1999
DOI: 10.1523/jneurosci.19-06-02381.1999
|View full text |Cite
|
Sign up to set email alerts
|

Spatial- and Task-Dependent Neuronal Responses during Real and Virtual Translocation in the Monkey Hippocampal Formation

Abstract: Neuropsychological data in humans demonstrated a pivotal role of the medial temporal lobe, including the hippocampal formation (HF) and the parahippocampal gyrus (PH), in allocentric (environment-centered) spatial learning and memory. In the present study, the functional significance of the monkey HF and PH neurons in allocentric spatial processing was analyzed during performance of the spatial tasks. In the tasks, the monkey either freely moved to one of four reward areas in the experimental field by driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 56 publications
8
95
2
1
Order By: Relevance
“…The place cell of the rodent HF is characterized by location-specific firing (O'Keefe and Conway, 1978;Eichenbaum et al, 1987;McHugh et al, 1996;Skaggs and McNaughton, 1998), and comparable HF neuron responses were also reported in monkeys (Ono et al, , 1993Nishijo et al, 1997;Matsumura et al, 1999). Place-cell activity is controlled by a salient cue or multiple spatial cues (e.g., O'Keefe and Conway, 1978;O'Keefe and Burgess, 1996), and remains stable over a long period Thompson and Best, 1990).…”
mentioning
confidence: 54%
“…The place cell of the rodent HF is characterized by location-specific firing (O'Keefe and Conway, 1978;Eichenbaum et al, 1987;McHugh et al, 1996;Skaggs and McNaughton, 1998), and comparable HF neuron responses were also reported in monkeys (Ono et al, , 1993Nishijo et al, 1997;Matsumura et al, 1999). Place-cell activity is controlled by a salient cue or multiple spatial cues (e.g., O'Keefe and Conway, 1978;O'Keefe and Burgess, 1996), and remains stable over a long period Thompson and Best, 1990).…”
mentioning
confidence: 54%
“…Comparable allocentric representations of physical location (Matsumura et al, 1999) and location of gaze (Rolls, Robertson, & Georges-Francois, 1997) have been reported in non-human primates. The recent discovery of place cells in the human hippocampus (Ekstrom et al, 2003) suggests that some of their properties (discussed below) may be applicable to understanding human spatial behavior.…”
Section: Forms Of Neural Representationmentioning
confidence: 90%
“…primates when navigating in natural environments, although electrophysiological studies have identified neurons in primate hippocampus corresponding to egocentric and to geocentric representations of space (e.g., Feigenbaum & Rolls, 1991;Matsumura et al, 1999).…”
Section: Brief Reportsmentioning
confidence: 99%